2017
DOI: 10.1186/s12871-017-0350-2
|View full text |Cite
|
Sign up to set email alerts
|

The efficacy and safety of mivacurium in pediatric patients

Abstract: BackgroundMivacurium is the shortest acting nondepolarizing muscle relaxant currently available; however, the effect of different dosages and injection times of intravenous mivacurium administration in children of different ages has rarely been reported. This study was aimed to evaluate the muscle relaxant effects and safety of different mivacurium dosages administered over different injection times in pediatric patients.MethodsSix hundred forty cases of pediatric patients, aged 2 m-14 years, ASA I or II, were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 13 publications
1
10
0
Order By: Relevance
“…This study showed that the grading of conditions for the LMA insertion-18 score of 0.15 mg/kg mivacurium was lower than 0.2 mg/kg and 0.25 mg/kg mivacurium in children during ambulatory urologic surgery. In addition, the onset times of 0.2 and 0.25 mg/kg mivacurium were shorter than 0.15 mg/kg mivacurium, which was consistent with the results of Zeng et al ( 2 ). However, the duration of clinical action and RI of a medium induction dose of mivacurium did not prolong or shorten the onset times compared with a small or increasing dose.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…This study showed that the grading of conditions for the LMA insertion-18 score of 0.15 mg/kg mivacurium was lower than 0.2 mg/kg and 0.25 mg/kg mivacurium in children during ambulatory urologic surgery. In addition, the onset times of 0.2 and 0.25 mg/kg mivacurium were shorter than 0.15 mg/kg mivacurium, which was consistent with the results of Zeng et al ( 2 ). However, the duration of clinical action and RI of a medium induction dose of mivacurium did not prolong or shorten the onset times compared with a small or increasing dose.…”
Section: Discussionsupporting
confidence: 92%
“…In recent years, mivacurium, which has a short elimination half-life, has been widely used in clinical general anaesthesia procedures in day-case surgery in China ( 2 , 10 , 21 ). Because it has a shortened waiting time after deep neuromuscular blockage compared with intermediate-acting cisatracurium and rocuronium, no direct effect on liver and kidney functions, rapid postoperative recovery, no accumulative effect in the body and a slight effect on circulation ( 9 , 10 ), mivacurium has become the main muscle relaxant used for paediatric anaesthesia in some countries ( 4 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Antihistamines block all these effects (72,78). It should be noted that occasional studies only reported average changes in histamine levels and/or mean arterial pressure, which sometimes did not achieve significance as a group (71,79,82,84). This does not mean that zero patients in the group suffered from an AE.…”
Section: Allergic-type Event Frequency and Mast Cell Dependencementioning
confidence: 99%
“…Consequently, the use of an agent with the shortest probable clinical duration may be helpful [ 91 - 93 ]. When compared with healthy control subjects, though there was no difference noted in the onset times, patients with Duchenne muscular dystrophy confirmed only a modest prolongation of the clinical effect of mivacurium [ 94 ].…”
Section: Prominent Role Of Alkaloids In Neuromuscular Junction Diseasesmentioning
confidence: 99%